Sexual orientation and gender identity in human rights law : jurisprudential, legislative and doctrinal references from the Council of Europe and the European Union (ICJ GenevaCH, 2007)
Presents a compilation of European jurisprudence, legislation and doctrine referring to sexual orientation and gender identity. Addresses references from both the Council of Europe and the European Union systems
Keywords: HUMAN RIGHTS